Business Ethics as Self-Regulation: Why Principles that Ground Regulations Should Be Used to Ground Beyond-Compliance Norms as Well - Norman, Wayne J. (2011)
Theories of business ethics or corporate responsibility tend to focus on justifying obligations that go above and beyond what is required by law. This article examines the curious fact that most business ethics scholars use concepts, principles, and normative methods for identifying and justifying these beyond-compliance obligations that are very different from the ones that are used to set the levels of regulations themselves. Its modest proposal—a plea for a research agenda, really—is that we could reduce this normative asymmetry by borrowing from the normative framework of “regulation” to identify and justify an important range of beyond-compliance obligations. In short, we might think of “self-regulation” as a language and a normative framework with some distinct advantages over other frameworks like stakeholder theory, corporate social responsibility, corporate citizenship, and the like. These other frameworks have been under attack in the business ethics literature of late, primarily for their vagueness and their disappointing inability to distinguish clearly between genuine beyond-compliance moral obligations, on the one hand, and charitable acts that are laudable but not morally obligatory, on the other.
Keywords: Market failure; Beyond-compliance obligations; Corporate Citizenship; Stakeholder Theory; Corporate Social Responsibility; Self-regulation; Regulation; Business Ethics